The Role of Co-Curricular Activities in Islamic Higher Education: Engaging Gen-Z with Developmental Theories - Yusnaini; Nuriman; Setiawan (International Journal on Higher Education Issues, 2025)
The 4.0 Era has revolutionized education through the digital transformation of academic systems and curriculum design. This study investigates the role of co-curricular activities in Islamic higher education and their potential to attract and engage Gen-Z. Theories of humanism, recreation, self-development, and rational choice emphasize the importance of integrating values into co-curricular frameworks. The research also highlights the challenges faced by Islamic institutions, including the limited integration of co-curricular activities and alignment with the career-oriented priorities of Gen-Z.A qualitative approach was employed through document analysis, observation, and in-depth, unstructured interviews to confirm and elaborate on the study's focus. The findings point to the need for co-curricular models that integrate Islamic values, fostering intellectual, social, and spiritual growth while simultaneously enhancing enrolment appeal.